2012
DOI: 10.1378/chest.11-2663
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism

Abstract: Pulmonary embolism (PE) is a common, often fatal, acute medical condition for which timely therapy can be life saving. The average annual incidence of acute PE in the United States is about 110 in 100,000 adults. The case fatality rate in the years prior to the introduction of anticoagulant therapy exceeded 30%; current estimates of case fatality are , 10%. 1,2 The accurate diagnosis of PE relies on clinical acumen and timely use of appropriate diagnostic studies. Indi viduals with PE who present with shock or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…[9, 21] All other admissions were considered to be weekday admissions. This is the definition used by NIS and cannot be modified.…”
Section: Methodsmentioning
confidence: 99%
“…[9, 21] All other admissions were considered to be weekday admissions. This is the definition used by NIS and cannot be modified.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have reported increased mortality with weekend or after-hour hospitalizations in stroke and myocardial infarction [22][23][24][25]. However, few have examined weekend discharge and its effect on postsurgical patient readmissions.…”
Section: Commentmentioning
confidence: 99%
“…Applying principles of the "weekend effect" to the discharge process after cardiac surgery may provide an alternative approach to readmission reduction [20,21]. The weekend effect phenomenon, which has been used to describe higher mortality in myocardial infarction, stroke, and cardiac arrest admissions that occur on the weekend or at night, has been attributed to lower staffing levels and higher physician turnover on off-hours [22][23][24][25]. Given the strong correlation between weekend admissions and outcomes after common conditions, we aimed to investigate whether such differences in staffing from the usual weekday routine would affect the discharge process for cardiac surgical patients.…”
mentioning
confidence: 99%
“… 14–16 Although the weekend effect may be a function of confounding by unmeasured differences in the severity of illness at the time of admission, others have hypothesised that differences in quality of care delivered between weekends and weekdays mediate this effect. 1 2 10 11 During the weekend, the hospital staffing may be reduced and/or less experienced medical staff may be working. In addition, restricted availability of diagnostic or therapeutic procedures leading to delays in care may influence patient outcomes.…”
Section: Introductionmentioning
confidence: 99%